Push-off mechanics in speed skating with conventional skates and klapskates - Houdijk, H.; de Koning, J. J.; de Groot, G.; Bobbert, M. F.; van Ingen Schenau, G. J. (Medicine & Science in Sports & Exercise, 2000)
Purpose: Personal and world records in speed skating improved tremendously after the introduction of the klapskate, which allows the foot to plantar flex at the end of the push-off while the full blade continues to glide on the ice. The purpose of this study was to gain insight into the differences in skating technique with conventional versus klapskates and to unveil the source of power enhancement using klapskates. Methods: Ten elite speed skaters skated four 400-m laps at maximal effort with both conventional and klapskates. On the straight high-speed film, push-off force and EMG data were collected. An inverse dynamics analysis was performed in the moving reference plane through hip, knee, and ankle. Results: Skating velocity increased 5% as a result of an increase in mean power output of 25 W when klapskates were used instead of conventional skates. The increase in mean power output was achieved through an 11-J increase in work per stroke and an increase in stroke frequency from 1.30 to 1.36 strokes·s-1. The difference in work per stroke occurs during the final 50 ms of the push-off. This is the result of the ineffective way in which push-off forces are generated with conventional skates when the foot rotates about the long front end of the blade. No differences in muscle coordination were observed from EMG. Conclusion: A hinge under the ball of the foot enhances the effectiveness of plantar flexion during the final 50 ms of the push off with klapskates and increases work per stroke and mean power output.